P146 Cleaning products and respiratory health outcomes in professional cleaners: a systematic review and meta-analysis. (December 2018) - Archangelidi, O; De Matteis, S; Jarvis, D
Abstract : Introduction/objectives: There is consistent evidence of increased respiratory health effects in professional cleaners; however, uncertainty remains on underlying causal agents, mechanisms, and respiratory phenotypes. We aimed to conduct a systematic review and meta-analysis of the available literature to characterise and quantify the impact of the cleaning-related respiratory health burden. Methods: We searched MEDLINE and EMBASE database and included studies that evaluated the association of at least one respiratory health outcome with exposure to cleaning products in adult professional cleaners. GRADE was used to appraise the quality of included studies. Results: We retrieved in total 897 articles, and after applying our inclusion criteria, 33 remained in the final review. The meta-analyses of population based cross-sectional and cohort studies showed positive associations between cleaning exposure and asthma risk: odds ratio (OR)=1.38 (95%CI: 1.06–1.79) (I 2 =0.0%) and OR=1.53 (95% CI: 1.29–1.82) (I 2 =0.0%), respectively (figure 1). Workforce studies were of lower precision with no overall statistically significant risk. Risk estimates were generally higher for self-reported, than for objectively assessed asthma. Very limited association was observed for exposure to cleaning products and rhinitis risk, whereas a significant association was found for chronic obstructive pulmonary disease (COPD) risk in two large cross-sectional studies. There was conflicting evidence for an association of bronchial-hyper-responsiveness (BHR) with cleaning agent exposure which was particularly prominent to ex-smokers. Cleaners did not show a typical atopic respiratory phenotype, nor increased fractionated exhaled nitric oxide (FENO). Conclusions: All studies lacked quantitative exposure assessment to cleaning products, but inclusion of such measures in further large prospective studies would help elucidate underlying causal mechanisms.